THE CHARACTERISTICS OF THE COMPETITIVE ANXIETY APPEREANCE AMONG THE PENTATHLON’ ATHLETES 14-19 YEARS - Melnik, E.V.; Borovskaya, N.I.; Seletsky A.V., А.V. (Modern Psychology, 2019)
This paper presents the interrelation of anxiety in pentathlon’s athletes different ages with the success of competitive activity/ Studies of anxiety have shown that among the components of success, and among the reasons for the failure in sports competition, a certain percentage belongs to the mental state, namely, the anxiety of the athlete before and during the competition. The problem is especially relevant for pentathlon athletes of adolescence and youth age, because in these periods negative emotions are experienced most vividly in the situation presenting to others, of self-disclosure. This is explained, on the one hand, the fact that these athletes tend excessively to critically assess themselves, but at the same time self-centered. All this determines the importance of the competitive anxiety study of young pentathlon athletes among the components of their psychological preparation.
Keywords: modern pentathlon; adolescents; psychological training; sports performance; anxiety